Static orthoses in the prevention of hand dysfunction in rheumatoid arthritis: a review of the literature. - Adams, J; Hammond, A; Burridge, J; Cooper, C (2005)
Static orthoses are recommended for individuals who have early rheumatoid arthritis (Scottish Intercollegiate Guidelines Network, 2002; College of Occupational Therapists, 2003). These orthoses aim to rest and immobilize weakened joint structures and decrease local inflammation (Janssen et al., 1990; Nicholas et al., 1982); correctly position joints (Nordenskiöld, 1990; Ouellette, 1991); minimize joint contractures (McClure et al., 1994); increase joint stability (Kjeken et al., 1995); relieve pain (Feinberg, 1992; Callinan and Mathiowetz, 1996; Kjeken et al., 1995) and improve function (Janssen et al., 1990; Pagnotta et al., 1998; Nordenskiöld, 1990). Wrist and hand orthoses have been routinely prescribed for individuals with rheumatoid arthritis (RA) for the last 30 years with limited evidence that they are effective in achieving their purported aims. This article reviews the possible deterioration in hand structure that can occur in RA and discusses the theoretical basis for the application of static orthoses in RA. The evidence for the effectiveness of four commonly used static orthoses is then examined.